Anthropomorphic Prosthetic Hand with Combination of Light Weight and Diversiform Motions - Xiaobei Jing; Xu Yong; Yinlai Jiang; Guanglin Li; Hiroshi Yokoi (Applied Sciences, 2019)
Most prosthetic hands adopt an under-actuated mechanism to achieve dexterous motion performance with a lightweight and anthropomorphic design. Many have been verified in laboratories, and some have already been commercialized. However, a trade-off exists between the dexterity and the light weight of such prosthetic hands. In general, current commercially available prosthetic hands usually consider one aspect at the expense of the other, such as obtaining diversiform hand motions but an increased weight, or achieving lightweight design but with limited motion functions. This study attempts to attain a balance between the two factors, by realizing diversiform hand motions while reducing the weight as far as possible. An anthropomorphic prosthetic hand is proposed with only three servomotors embedded in a human-sized palm, with multiple functions, such as a stable/adaptive grasp and passive hyperextension. The proposed hand can achieve 13 grasp types with over 80% of the grasp motions under the Cutkosky taxonomy, while it weighs only 132.5 g, at less than 36% of the prosthesis weight limitation based on the study of Kay et al.